2021
DOI: 10.1002/mawe.202000230
|View full text |Cite
|
Sign up to set email alerts
|

A study of corrosion performance of tinplate with different tin coating thickness in H2SO4solution

Abstract: The corrosion performance of tinplate with different coating mass in H2SO4 solution has been investigated by electrochemical measurements and scanning electron microscope observation. The results indicate that the tinplate with a higher tin coating mass exhibits better corrosion resistance than the sample with a lower tin coating mass due to that a lower tin coating mass may not uniformly cover the base steel surface with roughness or other defects. Besides, the amount of coating mass on tinplate can greatly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…One of the biggest problems faced by high-speed tin electrodeposition of low tin-coated products is: How to keep the consistent coating uniformity on the tinplate? 4,5 As is known to all, in the electrodeposition process, the existence of the tip effect (also called edge effect) often makes a thicker coating mass at the edge of the product. 6 As early as 1956, the research of Fumio Hine et al showed that when the electrodes were set far away from the wall of the electrolytic cell, the current was obviously concentrated in the cathode edge, and such current distribution would influence the horizontal coating distribution of the tinplate.…”
mentioning
confidence: 99%
“…One of the biggest problems faced by high-speed tin electrodeposition of low tin-coated products is: How to keep the consistent coating uniformity on the tinplate? 4,5 As is known to all, in the electrodeposition process, the existence of the tip effect (also called edge effect) often makes a thicker coating mass at the edge of the product. 6 As early as 1956, the research of Fumio Hine et al showed that when the electrodes were set far away from the wall of the electrolytic cell, the current was obviously concentrated in the cathode edge, and such current distribution would influence the horizontal coating distribution of the tinplate.…”
mentioning
confidence: 99%